Repetitive transcranial magnetic stimulation for hypokinetic dysarthria in Parkinson's disease enhances white matter integrity of the auditory-motor loop - Brabenec, Lubos; Simko, Patrik; Sejnoha Minsterova, Alzbeta; Kostalova, Milena; Rektorova, Irena (European journal of neurology, 2023)
BACKGROUND AND PURPOSE: In our previous study, repeated sessions of repetitive transcranial magnetic stimulation (rTMS) over the auditory feedback area were shown to improve hypokinetic dysarthria (HD) in Parkinson's disease (PD) and led to changes in functional connectivity within the left-sided articulatory networks. We analyzed data from this previous study and assessed the effects of rTMS for HD in PD on the diffusion parameters of the left anterior arcuate fasciculus (AAF), which connects the auditory feedback area with motor regions involved in articulation. METHODS: Patients were assigned to 10 sessions of real or sham 1-Hz stimulation over the right posterior superior temporal gyrus. Stimulation effects were evaluated using magnetic resonance diffusion tensor imaging and by a speech therapist using a validated tool (Phonetics score of the Dysarthric Profile) at baseline, immediately after 2 weeks of stimulation, and at follow-up visits at Weeks 6 and 10 after the baseline. RESULTS: Altogether, data from 33 patients were analyzed. A linear mixed model revealed significant time-by-group interaction (p = 0.006) for the relative changes of fractional anisotropy of the AAF; the value increases were associated with the temporal evolution of the Phonetics score (R = 0.367, p = 0.028) in the real stimulation group. CONCLUSIONS: Real rTMS treatment for HD in PD as compared to sham stimulation led to increases of white matter integrity of the auditory-motor loop during the 2-month follow-up period. The changes were related to motor speech improvements.
Keywords: White Matter; Transcranial Magnetic Stimulation; transkraniální magnetická stimulace; lidé; zobrazování difuzních tenzorů; Diffusion Tensor Imaging; Dysarthria; Parkinsonova nemoc; dysartrie; bílá hmota; Parkinson Disease; Humans